2017
DOI: 10.1111/and.12892
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life's dependence on socio-economic status and demographic characteristics among men with benign prostatic hyperplasia

Abstract: This study investigated the effect of socio-economic status (SES) on health-related quality of life (HRQoL) among persons with benign prostatic hyperplasia (BPH). The data were collected by way of surveying persons with BPH aged from 35 to 85 (937) and selected via random sample. The diagnosis was confirmed with the use of I-PSS questionnaires (8-19 points), OABq-AT (≥8 points) and daily urinations. A study on HRQoL was conducted using the SF-36 questionnaire. SES was evaluated using the patients' ambulance ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Fowke et al found men with any college degree sustain risks of 1.41 times (95%CI 1.21-1.65) compared with high school or general education diploma [36]. Study by Kosilov et al revealed that prevalence of BPH declined in sequence among master s degreeþ, university degree, high school and less than high school [37]. Our study shows participants with elementary school, middle school, high school and college degree or above sustain adjusted odds ratios of 1.41 (95%CI 1.15-1.73), 1.55 (95%CI 1.25-1.92), 2.32 (95%CI 1.77-3.06) and 2.74 (95%CI 2.07-3.62) (p < 0.001), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Fowke et al found men with any college degree sustain risks of 1.41 times (95%CI 1.21-1.65) compared with high school or general education diploma [36]. Study by Kosilov et al revealed that prevalence of BPH declined in sequence among master s degreeþ, university degree, high school and less than high school [37]. Our study shows participants with elementary school, middle school, high school and college degree or above sustain adjusted odds ratios of 1.41 (95%CI 1.15-1.73), 1.55 (95%CI 1.25-1.92), 2.32 (95%CI 1.77-3.06) and 2.74 (95%CI 2.07-3.62) (p < 0.001), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…BPH affects HRQOL by inducing psychological stress in patients due to anxiety and deterioration of their social function. The more severe the symptoms of BPH, the lower the HRQOL becomes; HRQOL of patients with BPH who experience worsening symptoms due to aging has been shown to be significantly reduced [ 10 , 11 , 12 ]. Particularly, as HRQOL acts as a major factor causing behaviors to manage diseases, improving the HRQOL can induce the treatment pursuing behavior of patients with BPH.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, given the existing study results that those engaged in professions have a lower prevalence of BPH, future studies should conduct an analysis of the quality of life according to the occupation of the patients with BPH. [ 38 , 41 ] Second, since an analysis of the quality of life has not been performed in the patients with BPH according to treatment method, it seems that future research may suggest therapies that can improve the quality of life of patients, through further analyses. Third, additional studies including a control group without BPH or comorbidities are needed.…”
Section: Discussionmentioning
confidence: 99%